Floating right atrial thrombus associated with submassive pulmonary embolism - Vukmirović, Mihailo; Babić, Blagoje (Vojnosanitetski pregled, 2025)
Introduction. Massive free-floating thrombi in the right heart are rarely seen in everyday clinical practice and are most often the result of embolization by thrombotic masses from the veins of the lower extremities. Thrombi in the right heart represent a great risk for life-threatening submassive or massive pulmonary embolism, making early diagnosis and adequate treatment crucial. Case report. We present the case of a 56-year-old male patient who developed submassive pulmonary embolism as a consequence of a large floating thrombus in the right heart, rapidly diagnosed by echocardiography. On admission, the patient was hemodynamically stable with a blood pressure of 140/100 mmHg. The initial risk assessment was performed using the Pulmonary Embolism Severity Index score, which was 86, that placed the patient in class III, indicating a moderate risk of mortality within 30 days of the event. Given the patient’s hemodynamic stability and the massive size of the right heart thrombus, thrombolytic therapy was avoided due to the risk of dispersal of thrombotic masses, additional embolization, and hemodynamic load of the pulmonary circulation. Catheter-based procedures were not feasible as such interventions are not performed at the treating institution. Due to all of the above, it was decided that surgical thrombectomy was the most appropriate and safest solution for the patient. A surgical thrombectomy was successfully performed. The postoperative course was uneventful, and the patient recovered quickly. Conclusion. Massive pulmonary embolism concomitant with right heart thrombosis is associated with high mortality. This case highlights the importance of rapid diagnosis, a multidisciplinary approach, timely decision-making, and individualized treatment, which reduce mortality in these patients.
Keywords: diagnosis; echocardiography; heart atria; pulmonary embolism; thrombectomy; thrombosis